Health Education and the Increase in TB Patient Medication Compliance - Gunawan, Fahri; Nursasi, Astuti Yuni (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Tuberculosis (TBC) is an infectious disease that worsens individual health and is the leading cause of death in the world. Long TBC treatment requires interaction from TBC sufferers who require intervention in medication adherence. Compliance is an important factor in TBC treatment, therefore WHO made DOT to monitor TBC treatment. One method that has been proven to have a positive effect is health education interventions to increase adherence to anti-tuberculosis treatment in TBC patients. Educational interventions are aimed at providing patient knowledge and understanding of the disease process and the risks and benefits associated with medication adherencePurose: To get an overview of how the health education model is used to improve adherence to taking anti-tuberculosis drugs in TBC patientsMethod: writing using a Systematic Review with a literature search carried out in accordance with the preparation of research questions using the PICO formula. The data base used is Proques, Scoopus, Embase, Clinicalkey with articles used in full text with a publication period from 2018-2023Results: There were 7 articles related to health education interventions on adherence to taking OAT in Tuberculosis patients.Conclusion: Increasing the knowledge of TBC patients about TBC disease with health education can change the beliefs and perspectives of TBC sufferers towards the disease so that it can show increased adherence to taking antituberculosis drugs in TBC patients